2011
DOI: 10.1111/j.1439-0426.2010.01645.x
|View full text |Cite
|
Sign up to set email alerts
|

Pallid sturgeon size structure, condition, and growth in the Missouri River Basin

Abstract: Summary We synthesized wild and stocked pallid sturgeon Scaphirhynchus albus capture data collected in four recovery areas of the Missouri River during 1998–2007, providing the first basin‐wide analysis of size structure, growth, and condition. Proportional size distribution (PSD) values ranged from 20 to 33 and were indicative of past stockings given the continued lack of natural recruitment. A new weight‐length regression derived from 2268 captured wild (8%), hatchery‐stocked (75%), and unknown origin (16%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…Hatchery-reared fish in the lower Missouri River were growing (Shuman et al 2011), exhibiting migratory behavior and reaching sexual maturity DeLonay et al 2012;Steffensen et al 2013a). The numbers of reproductive fish in the lower Missouri River was increasing prior to 2013; however, the proportion of reproductive fish collected annually continues to decrease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hatchery-reared fish in the lower Missouri River were growing (Shuman et al 2011), exhibiting migratory behavior and reaching sexual maturity DeLonay et al 2012;Steffensen et al 2013a). The numbers of reproductive fish in the lower Missouri River was increasing prior to 2013; however, the proportion of reproductive fish collected annually continues to decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Fort Peck Dam [rkm 2850.9] to the headwaters of Lake Sakakawea [rkm 2523.5]). Shuman et al (2011) detected differences in Kn by incremental PSD Figure 2. Annual mean ( §SE) relative condition factor (Kn) by gender and reproductive assessment for adult (> 800 mm) pallid sturgeon transported to local hatcheries as potential brood fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature shows that for the multi-model inference approach applied to individual growth, it is not unusual that different candidate growth models yield equal values of AIC (Rogers-Bennett et al 2007, Flores et al 2010, Helidoniotis et al 2011). Several studies also have shown that the AIC estimates of the candidate growth models were very close; the magnitude of the change can be < 0.1 (Araya & Cubillos 2006, Shelton et al 2006, Farrell et al 2010, Barreto et al 2011, Grist et al 2011, Mercier et al 2011, Shuman et al 2011. Markaida et al (2005), using mark-recapture data of D. gigas, showed that the daily growth rate diminishes for older individuals; their study analyzed squid between 46 and 80.7 cm ML, and the daily growth rate changed from 1.5 to 1.0 mm d −1…”
Section: Discussionmentioning
confidence: 99%
“…Stocking in the middle Mississippi River has not been as intensive compared with the Missouri River and was limited to the 1992 and 1997 year class (T. W. Huenemann, unpublished data). Hatchery‐reared S. albus are surviving (Steffensen et al ., ; Rotella, ; Steffensen et al ., ) and growing (Shuman et al ., ) and along with a remnant wild population, comprise the current S. albus population.…”
Section: Introductionmentioning
confidence: 97%